Bilateral Macular Roth Spots as a Manifestation of Subacute Endocarditis - Karolina Ceglowska; Katarzyna Nowomiejska; Agnieszka Kiszka; Michael J. Koss; Ryszard Maciejewski; Robert Rejdak (Case Reports in Ophthalmological Medicine)
A 42-year-old man presented with a 2-day history of impaired vision in the right eye (OD). The best corrected visual acuity (BCVA) (LogMAR) was 1.1 for the right eye and 0.0 for the left eye (OS). Fundus examination revealed white-centered hemorrhages resembling Roth spots in both macular regions. The spectral-domain optical coherence tomography (SD-OCT) showed intraretinal pseudocysts and hyperreflective deposits in the areas corresponding to the Roth spots. Conducted blood tests revealed elevated D-dimer concentration, increased total number of neutrophils, high C-reactive protein concentration, and elevated erythrocyte sedimentation rate. Procalcitonin concentration, platelet count, and body temperature were within normal ranges. A blood culture was ordered and yielded Streptococcus mitis and intravenous antibiotics were started immediately. The patient started complaining of chest and left calf pain. The systemic examination revealed infective endocarditis accompanied by bicuspid aortic valve and paravalvular abscess formation. The patient underwent cardiac surgery with mechanical aortic valve implantation. After recovery, the patient’s visual acuities improved fully. Control ophthalmic examination, including SD-OCT, showed no abnormalities.